Systematic Literature Review (SLR): Pengaruh Pendidikan Kewirausahaan Dan Locus Of Control Terhadap Intensi Berwirausaha - Agnes Natalia Dwi Ani; Riza Yonisa Kurniawan (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
Conducting a literature review study on the locus of control and entrepreneurial education effect on entrepreneurial intention was the objective of this study by using Systematic Literature Review (SLR) as the research method. Documenting all articles related to this study was done to gather data. A total of 22 articles sourced from Sinta and Google Scholar was utilized in this study. From this study, it was found that entrepreneurial intention was significantly influenced by locus of control and entrepreneurial education. The skills, knowledge, and mental attitudes required in entrepreneurship were obtained through entrepreneurial education, while internal locus of control encouraged personal responsibility, independence, risk-taking, and the ability to overcome failure. The literature review results also found that the development of internal locus of control and entrepreneurial education could be implemented as strategies to enhance individual entrepreneurial intention. Therefore, it was important for educational institutions and governments to enhance entrepreneurial education, develop mentorship programs, and create better entrepreneurial opportunities in facilitating the development of individual entrepreneurial intention.